EFFECTS OF MACA (LEPIDIUM MEYENII WALP) POWDER ON SERUM INDICES AND METABOLIC RESPONSES IN RACEHORSES - T. Bilal; I. Abas; S. Korkmaz; A. Ates; O. Keser; C. Kumas (Journal of Animal and Plant Sciences, 2016)
Eighteen racehorses, 6.5±1.17 years old, were divided into three groups. During 45 days, control group was fed basal diet, experimental groups M50 and M75 were fed basal diet plus 50 and 75 g/day maca extract, respectively. There were no significant differences between groups for initial and final body weight, average daily feed intake and blood hemogram values during the study. On day 45, while M75 had higher aspartate transaminase level than M50, gamma-glutamyl transpeptidase level in this group were higher than both control and M50 (p<0.05). M75 had lower Mg level than control (p<0.037). After feeding, M50 had higher adiponectin level than control and M75 at 30th min. (p<0.05). Insulin level in M50 and M75 were lower than control at 60th min., but it was higher in M50 than M75 at 120th min. (p<0.003). Thyroid stimulating hormone levels in M50 were lower than control at  60th  min. before feeding and were higher than M75 at 15th  min. after feeding (p<0.05). Triiodothyronine concentrations were higher in M75 than other groups (p<0.001). Similarly, M75 had higher thyroxine concentration than control and M50 during the study (p>0.05). The differences between groups were found statistically significant only at 60th min.
Keywords: Horses; Lepidium meyenii Walp; Maca powder; Metabolic responses; Serum indices